Provider Counseling and Women's Family Planning Decisions in the Postpartum Period [30A]. (May 2017) - Goulding, Alison N.; Bauer, Anna E.; Bryant, Amy G.; Stuebe, Alison M.
Abstract : INTRODUCTION: Provider counseling may influence women's family planning decisions. METHODS: We conducted an anonymous, Internet-based survey of adult women regarding multiple topics, including prenatal/postpartum care and family planning. Participants were included if they delivered a singleton infant within the last 3-9 months and breastfed at any time. We used multivariable logistic regression to quantify the association between quantity of provider counseling (indexed as number of family planning topics from 0-6 discussed by a healthcare provider) and women's decisions regarding contraception and birth spacing. RESULTS: From January to May 2016, 3, 010 women completed the survey and met inclusion criteria. Among this group, 2, 684 (89.2%) were white and 2, 166 (72.0%) completed at least a four-year college degree. 1, 417 (47.1%) desired an inter-pregnancy interval (IPI) greater than two years, and 599 (19.9%) used long-acting reversible contraception (LARC) or sterilization. The majority of women (n=1, 595, 53.0%) had received counseling on 3-6 family planning topics (defined as "more counseling" in regression models). Women who received more counseling were more likely to use LARC or sterilization (AOR 1.32, 95%CI 1.08-1.61) but were not more likely to desire an IPI greater than two years (AOR 0.97, 95%CI 0.81-1.15). Desired IPI modified the association between provider counseling and contraception (P=0.06 for interaction): Among those desiring an IPI greater than two years, more counseling was associated with more use of LARC or sterilization (AOR 1.56, 95%CI 1.22-2.01), but this was not observed among those desiring a shorter IPI. CONCLUSION: Contraceptive decisions depend on both provider counseling and patient goals.